スポーツと経済開発 - マンデル J.R (スポーツ社会学研究, 2012)
There is little evidence that increased sport participation promotes development. Nevertheless the growth of sport is valuable because it provides individuals with an enhanced opportunity to engage in an activity that they find pleasurable. The growth of sport therefore more nearly resembles an act of consumption than investment. Instead of treating sport as an act of investment with positive spillovers, this paper considers sport in Bangladesh to be a dependent variable. It uses cross sectional data to test the hypothesis that Bangladesh’s economic underdevelopment is causal in explaining why sport participation in the country is at a low level and that this inadequacy is even more marked for girls than boys. An examination of data does suggest that Bangladesh’s poverty is causal and that if the country’s economy modernizes, sport participation will increase and gender inequality will decline. In recent years Bangladesh has seen its garment and apparel industries expand. But these are low labor productivity, low wage sectors. They therefore have not had a strong positive effect on the level of sport participation or in reducing gender inequality. What Bangladesh requires for sport participation to grow and for women to become more personally empowered is success in economic modernization. The country has to increase its technological capability. To do so it will have to greatly enhance the opportunity for the people in the country to attain a secondary school level of education. スポーツ参加が増えることが開発を促進するという主張を裏付ける証拠はなきに等しい。しかしながら、スポーツでの発展は、人々が楽しめる活動に接する機会を個々に増やす点に価値がある。それゆえ、スポーツでの発展は、投資よりも消費行動に近いものと考えられる。 本論文では、スポーツを剰余をもたらす投資行動として扱うのではなく、バングラデシュでのスポーツを従属変数とみなしている。横断的なデータ分析により、バングラデシュの経済が発展途上であるから、その国でのスポーツ参加も低レベルに留まっているのだという仮説が検証され、またこうした機能不全が男性より女性に多くみられることが明らかになった。 データを吟味することで、バングラデシュの貧困こそが元凶であって、もしこの国が近代化されれば、スポーツ参加が増加し、性的不平等が低減されることが示唆された。 近年、バングラデシュでは衣料・アパレル産業が成長している。しかし、生産性は低く、賃金も低いままである。したがって、スポーツ参加を活性化するにも、性的不平等を低減するにも、それは役立っていない。 スポーツ参加を増やすにも、女性のエンパワメントを実現するにも、バングラデシュで必要なのは、経済の近代化に成功することである。彼らは技術力を高める必要がある。そうすることで、かの国の人々が中等レベルの教育を受ける機会を大幅に拡大しなければならない。